Regulatory Effect of Mung Bean Peptide on Prediabetic Mice Induced by High-Fat Diet - Li, Lina; Tian, Yu; Zhang, Shu; Feng, Yuchao; Wang, Haoyu; Cheng, Xiaoyu; Ma, Yantao; Zhang, Rui; Wang, Changyuan (Frontiers in Nutrition, 2022)
Dietary supplementation of mung bean peptides（MBPs）has many health benefits, but its effect on prediabetes and gut microbiota imbalance caused by high-fat diet (HFD) has not been thoroughly studied. Dietary supplementation of MBPs for five weeks significantly reduced high-fat diet-induced body weight gain, hyperglycemia, hyperlipidemia, insulin resistance, inflammation and oxidative stress in mice, and alleviated liver and kidney damage. In addition, it significantly reversed HFD induced gut microbiota imbalance, increased gut microbial diversity and decreased Firmicutes and Bacteroidetes abundance in prediabetic mice. We also found that Lachnospiracea_NK4A136 group and Lactobacillus may be important eubacterium to alleviate the clinical symptoms of prediabetes. According to PICRUSt2 analysis, the changes of intestinal microflora induced by MBPs diet intervention may be related to down-regulation of gene expression such as rocR, lysX1, and grdA, and regulation of seven pathways such as pyruvate, succinic acid and butyric acid. At the same time, it was found that 17 kinds of significant change intestinal microorganisms such as Akkermansia, Roseburia, and Ruminiclostridium were significantly correlated with 26 important differential metabolites such as D-glutathione, anti-oleic acid and cucurbitacin.In general, these results showed that MBPs as a food-borne strategy, played an important role in the management of HFD induced prediabetes.